A new computational method for structural vibrations in the medium-frequency range - Ladevèze, Pierre; Arnaud, Lionel (Computer Assisted Methods in Engineering and Science, 2000)
In the paper a new approach for the computation of slightly damped elastic structural vibrations over the medium frequency range is proposed. The effective quantities (deformation energy, vibrational intensity, etc ... ) are evaluated after resolution of a small system of equations that does not in any way result from a fine "finite element" discretisation of the structure.